Generic Strategies and sustainability of Financial Performance of Nepalese Enterprises (Pravaha, 2018)
The purpose of this paper is to examine the relationship between firm strategy and sustainability of financial performance of Nepalese Enterprises. The research design adopted in this study consists of descriptive and causal-comparative research designs to deal with the various issues raised in this study. Secondary data has been used for this study which was collected from annual audit report of concerned organization of manufacturing and hotel industrities from fiscal year 2000/01 to 2014/15. Factor analysis, descriptive statistics, correlation analysis, and regression analysis are different statistical tool that has been used for this study. Cost leadership and differentiation strategies has been constructed from selling, general, and administrative expenses divided by sales; sales divided by cost of goods sold; capital expenditure on property, plant, and equipment divided by sales, and net book value of plant and equipment; divided by sales variables through factor analysis. By regressing return on assets of future period against on return on assets, interaction of cost leadership strategy with return on assets, interaction of differentiation strategy with return on assets variables. The analysis shows that the enterprises adopting higher selling, general and administrative expenses in association with higher gross profit margin are pursuing differentiation strategy whereas, higher investment on property, plant and equipment along with their existing higher book value of plant and equipment indicates that they are following cost leadership strategy. When organization is following cost leadership and differentiation strategy both positive effect on sustainability of financial performance of Nepalese enterprises. Out of cost leadership and differentiation strategy, cost leadership is better than differentiation strategy to increase financial performance of Nepalese enterprises. Pravaha Vol. 24, No. 1, 2018, page: 39-49